PRODUK INOVASI MIE KELOR (MORINGA OLEIFERA) SEBAGAI UPAYA PENCEGAHAN STUNTING DESA BABUL MAKMUR, KECAMATAN SIMEULUE BARAT, KABUPATEN SIMEULUE - Yulia Novita; Teuku Athaillah; Hasanuddin Husin; Mahmudin Marbun; Zulyaden Zulyaden (LPPM Universitas Bina Bangsa, 2022)
Village Babul Makmur, districts Simeulue Barat, district Simeulue is one of the expansion villages. The community already has adequate health knowledge, but the villagers Babul Makmur this has not paid attention to the problem of nutritional intake due to lack of knowledge and economic problems. Therefore, Moringa leaf as a plant resource that is quite easy and often found in this region can be one of the raw material for innovative producers in an effort to prevent stunting and fulfill nutrition for pregnant women and children.Moringa leaves are processed into Moringa noodles which are made from Moringa leaves which contain high nutrients, especially protein and calcium. The partners of this activity are the village community Babul Makmur.The processing of Moringa noodle innovation products is carried out through several methods, namely (1) production training; (2) assistance in making Moringa Noodles made from Moringa leaves until Moringa leaf Noodles are produced; (3) distribution of Moringa leaf noodles to the community, especially mothers and children.In general, this activity is quite good in helping the problems faced by the village community Babul makmur, namely to fulfill nutritional intake so as to avoid stunting problems. Abstract A maximum of 150 Indonesian words printed in italics with Cambria 10 point. The abstract should be clear, descriptive and should provide a brief overview of community service issues undertaken / researched. Abstracts include reasons for the selection of topics or the importance of research topics / community service, methods of research / devotion and outcome summary. The abstract should end with a comment about the importance of the result or a brief conclusion